Exercise and Crohn’s Disease: Speculations on Potential Benefits - Victor Ng; Wanda Millard; Constance Lebrun; John Howard (Canadian Journal of Gastroenterology)
Crohn’s disease (CD) is a chronic inflammatory bowel disease that affects nearly one million people in the United States and Canada. While current pharmaceutical treatments are effective in controlling symptoms, patients continue to experience a reduced quality of life (QOL). Based on preliminary studies, QOL in CD patients may be improved by engaging in physical activity. Exercise may decrease CD activity and reduce psychological stress. Current research also suggests that low-intensity exercise does not exacerbate gastrointestinal symptoms and does not lead to flare-ups. Furthermore, exercise appears to reduce CD symptoms and improve QOL. In summary, physical activity may be beneficial to certain patient groups, but more studies are needed before broad recommendations can be made.